Dietary Curcumin and Health Effects - Masella, Roberta; Cirulli, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue provides twelve contributions, of which three original articles, seven narrative reviews, one systematic review, and one meta-analysis that, altogether, offer a multifaceted and multidisciplinary overview that allows to draw a picture as intriguing and fascinating as possible on the benefits of curcumin and also to suggest potential fields of activities still to be explored. Among the biological activities exerted by curcumin, the anti-oxidative and anti-inflammatory properties reported in many studies make it a potential effective tool in preventing and counteracting chronic-degenerative diseases, very often associated with obesity and aging, such as cardiovascular diseases, T2D, metabolic dysfunctions, neurodegenerative diseases, and cancer, all of them characterized by the presence of oxidative and inflammatory processes. The main concerns that arise from the evaluation of the preventive/therapeutic effects of curcumin are, first of all, the still small number of randomized placebo-control studies available; in addition, small sample sizes have generally been considered, and different protocols and different formulations as well as different routes of administration of curcumin have been used. Thus, it is quite difficult to compare the results and to provide a standard protocol for the use of this promising natural compound. For these reasons, and taking in account the growing use of curcumin by the general population, further investigations to confirm and expand current findings are mandatory and research on curcumin and its effects on human health have to be fostered and promoted.